O problemowym nauczaniu literatury w szkole średniej = The Problem Teaching of Literature in a Secondary School - Słowiński, Lech (1922-2005) (Zielona Góra: Wyższa Szkoła Pedagogiczna)
The modern didactics considers only such methods of teaching and learning which help to initiate various kinds of pupils activity (intellectual, sensorimotor, emotional, verbal, and receptional) which train them in independent thinking and in efficient activity. One of the methods that fulfils those requirements is the method of problem teaching, often used in teaching Polish language and literature.
Keywords: literatura polska - nauczanie; szkolnictwo ponadpodstawowe; szkolnictwo polskie